Analisis Efektivitas Teknik Pendekatan Cognitive Behavioral Therapy in the Zone Toxic Relationship - Habsy, Bakhrudin All; Malora, Popo Indra; Walidah, Zianah; Livi, Ratna Nur (Lembaga Yasin AlSys, 2024)
Counseling Cognitive Behavior Therapy is an emotional activity that perceives someone else's feelings about that person's point of view. of the person without knowing their identity. Behavior therapy also introduces group counseling with cognitive restructuring techniques. Not only is it that teenagers also experience developmental periods especially in the ability to choose careers for their future. Cognitive Behavior Therapy also helps to solve career problems of students.nThe role of guidance and counseling to help students is with a cognitive behavioral approach. Toxic Relationships have a negative impact on others well being of every individual. Toxic relationships affect adolescent mental health . Toxic relationships can be avoided through increased knowledge. Not a few teenagers engage in the environment of friendship, which causes teenagers to experience social life problems such as the negative impact of friends who socialize with others and people who are friendly with them. Cognitive behavior counseling is also an approach between counseling by focusing on unpleasant or adverse events. The aim of this study was to explain how counselor approaches in cognitive behavioral therapy wants to approach the counselor so that it can be more confident and focus on not having bad thoughts that make him uncomfortable. Such events occur so often that adolescents are not offended by the solutions given and help adolescents solve their individual problems.